HUBUNGAN MUTU PELAYANAN KEPERAWATAN DENGAN TINGKAT KEPUASAN PADA KLIEN STROKE DI RSUD WATES - Nurcahyono, Arif; Arini, Sri; Dias, Khristina (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Nursing care is an integral part of medical services which plays a big role towards a nursing quality of a hospital. If they are fulfilled, clients' satisfaction will be achieved. Objective: To find out the correlation between nursing care quality and level of satisfaction of clients with stroke in RSUD Wates. Method: This research is descriptive analytical research with cross sectional design. Thirty (30) samples were taken using accidental sampling technique. Data were taken using questionnaire and analyzed using Kendall Tau test. Result: Fifty percent (50%) of the respondents of nursing care. Seventy percent (70%) of them felt satisfied with nursing care given by RSUD Wates. Based on the result of the Kendall Tau statistical test, it was found that the correlation coefficient is 0.408 with significance 0.016 (? < 0.05). Conclusion: There is correlation between nursing care quality and level of satisfaction of clients with stroke in RSUD Wates. It is expected that nurses in RSUD Wates improve the nursing care quality in RSUD Wates so that clients' satisfaction is achieved and fulfilled. Keywords: Nursing Care Quality, Satisfaction, Clients with Stroke